A shared inhibitory circuit for both exogenous and endogenous control of stimulus selection - Mysore, Shreesh P. (2013)
The mechanisms by which the brain suppresses distracting stimuli to control the locus of attention are unknown. We found that focal, reversible inactivation of a single inhibitory circuit in the barn owl midbrain tegmentum, the nucleus isthmi pars magnocellularis (Imc), abolished both stimulus-driven (exogenous) and internally-driven (endogenous) competitive interactions in the optic tectum (superior colliculus in mammals), which are vital to the selection of a target among distracters in behaving animals. Imc neurons transformed spatially precise multisensory and endogenous input into powerful inhibitory output that suppressed competing representations across the entire tectal space map. We identified a small, but highly potent, circuit that is employed by both exogenous and endogenous signals to exert competitive suppression in the midbrain selection network. Our findings reveal, for the first time, a neural mechanism for the construction of a priority map that is critical for the selection of the most important stimulus for gaze and attention.